Investigating the effectiveness of Singapore's environmental policies and initiatives in cultivating pro-environmental behaviours - Chia, Kai Tiak (Nanyang Technological University, 2023)
In pursuit of sustainable living and development, the Singapore government has implemented environmental policies and initiatives to inspire citizens to develop greater pro-environmental interest. While citizens possess increasing environmental awareness, inculcations of pro-environmental behaviours (PEBs) are lacking, signifying a mismatch between policy outcomes and objectives that Singapore’s environmental policies and initiatives were set to achieve. This study aims to assess the effectiveness of Singapore’s environmental policies and initiatives by understanding citizens’ perspectives of policy designs and implementations, and individual and contextual enablers and/or barriers that aid/inhibit citizens’ PEBs cultivation. The findings indicate that Singapore’s environmental policies and initiatives fail to consider citizens’ characteristics, lifestyles, and socioeconomic statuses, resulting in poor environmental reactivity. Additionally, limited communication objectives and avenues and inadequate citizen involvement in environmental policymaking deprive the development of environmental sensibilities and ownership. Policymakers may benefit from the findings by intensifying public outreach to exercise participatory engagement, exercising strategic communication and environmental education to inspire intrinsic motivations within individuals, and rendering necessary provisions to support citizens in cultivating PEBs.